The Curious Incident of the Franc in the Gambia: Floating Exchange Rates and the British Imperial Monetary System in the 1920s - Leigh Gardner (African Economic History Network (AEHN), 2014)
In 1922, the British colonial administration in the Gambia demonetized the French five franc coin, which had been legal tender since 1843. The cost of the demonetization was equal to a year's revenue, and undermined the stable fiscal position built up over previous decades. The floating exchange rates of the 1920s have long been a fruitful topic of research in European monetary history. Less attention has been paid to the impact of floating on colonial territories in the periphery. This paper uses the rather curious case of a British colonial administration paying to support the local value of the franc to illustrate that the 1920s are an equally useful period in the study of colonial monetary systems. A key aim of imperial governments was to ensure convertibility between colony and metropole, but local conditions in individual colonies often required compromises which went unnoticed until exchange rates became unstable.
Keywords: N17; N27; N97; 330; Africa; economic history; monetary systems; colonialism